Poly(l-lactic acid) Janus Shape Memory Membranes with Uniform Vertically Penetrative Channels and Slit Pores for Enhanced Fog Collection Synergistic Effect of Transport through Membranes and Sequential Sliding Behaviors of Water Droplets - Zhang, Liang (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this work, poly(l-lactic acid) (PLLA) Janus shape memory membranes with uniform vertically penetrative channels (SMEUVs) with slit pores have been fabricated with the help of template-assisting spray-coating and uniaxial tension at high temperature. During fog collection, superhydrophobic and hydrophilic surfaces act as the front (fog-facing) side and back side, respectively, in which the structural characteristics play essential roles. On one hand, the vertically penetrative channels in SMEUVs and the special pore geometry contribute to lower resistance, accelerating the transport of captured water through membranes (from the superhydrophobic side to the hydrophilic side). On the other hand, the movement of water droplets along the back side has been guided by the oriented structures of slit pores, promoting the detachment of droplets from the hydrophilic surface. Their synergistic effect removes captured water in a timely manner and provides fresh sites for the subsequent nucleation of water, enhancing fog collection performance. As a result, the optimal specimen (Janus SMEUVs with a draw ratio of 2.5, placed in the parallel direction) exhibits a much higher water collection rate (∼6×) relative to references (superhydrophobic and hydrophilic membranes). Our results are significant for sustainable development in view of both fog collection in arid regions and the biodegradability of PLLA